Carbonic anhydrase activation profile of indole-based derivatives. (1st January 2021) - Barresi, Elisabetta; Ravichandran, Rahul; Germelli, Lorenzo; Angeli, Andrea; Baglini, Emma; Salerno, Silvia; Marini, Anna Maria; Costa, Barbara; Da Pozzo, Eleonora; Martini, Claudia; Da Settimo, Federico; Supuran, Claudiu; et al.
Abstract: Carbonic Anhydrase Activators (CAAs) could represent a novel approach for the treatment of Alzheimer's disease, ageing, and other conditions that require remedial achievement of spatial learning and memory therapy. Within a research project aimed at developing novel CAAs selective for certain isoforms, three series of indole-based derivatives were investigated. Enzyme activation assay on human CA I, II, VA, and VII isoforms revealed several effective micromolar activators, with promising selectivity profiles towards the brain-associated cytosolic isoform hCA VII. Molecular modelling studies suggested a theoretical model of the complex between hCA VII and the new activators and provide a possible explanation for their modulating as well as selectivity properties. Preliminary biological evaluations demonstrated that one of the most potent CAA 7 is not cytotoxic and is able to increase the release of the brain-derived neurotrophic factor (BDNF) from human microglial cells, highlighting its possible application in the treatment of CNS-related disorders.